Efektivitas Pengembangan Modul Penuntun Praktikum Histologi Berbasis QR Code Terhadap Peningkatan Pemahaman Mahasiswa - Inayati, Rizqa; Hasanah, Nurul; Azmul Fauzi, Andri; Najah Rusyada, Gozin (METIK JURNAL, 2024)
Education is one of the fields that includes the field of teaching and learning. The teaching and learning process requires important components, one of which is teaching materials in the form of a practical guidance module. The existence of a practical guidance module during the practicum can help students understand and understand the practical material. This study aims to develop teaching materials in the form of a practical guidance module which is expected to improve students' understanding of the practical material, especially the Histology practicum. The development research method used in this study is the Research and Development (R&D) method with a total of 100 subjects of the 2024 Medical Study Program students. The instrument in this study was a questionnaire in the form of a gform. The questionnaire consisted of a validation questionnaire from material experts and media experts, as well as pre-test and post-test questions. The results of the pre-test and post-test were analyzed using the Wilcoxon and N-gain tests with SPSS. The assessment of the material expert and media expert validators showed a value of 86% and 92%, indicating that the module was very valid and could be used without revision. The Wilcoxon Test results show an Asymp.sig value of 0.000, indicating that there is an average difference between the pretest and post-test scores. The N-gain test results show an N-gain score of 84, indicating that the module effectively improves the understanding of students in the 2024 batch of the Medical study program with an increase in the level of understanding in the high category.